(untitled) (Research, Society and Development, 2023)
The phenomenon of population aging is growing in contemporary society, and despite the alarming increase in the number of elderly people in the world, many individuals intend to advance the years without necessarily aging, that is, contemplate the extension of life, however, do not aim to go through the deleterious processes of aging. In this sense, medicine, along with other areas of health and technology, seeks to develop interventional methods and practices aimed at rejuvenation. Thus, studies, with compounds, such as beta-hydroxybutyrate, and substances, such as probiotics and phytobioactives, have shown promise for the anti-aging effect sought. However, the lack of acceptance of the natural aging process and the true efficacy and safety of carrying out these interventions in health transform the interventional action into a constant state of risk to the health of the individual. Therefore, this article, through a literature review of the last five years (2018 to 2022),in the databases: Virtual Health Library(BVS), Scientific Electronic Library Online (ScieLO),National Library of Medicine (PubMed),EbscoHost, and Google Scholar and data from the Population Division by the UN Department of Economic and Social Affairs, aimed to analyze the possible relationships between the anti-aging process and health-related risks in adults aged 30 to 50 years , in order to clarify doubts regarding the feasibility of interventional procedures.20 articles were identified, which revealed that there are, in evident, medical applications that can be use for rejuvenation, however, these need certain defined care and dosages so that its effectiveness is truly viable without causing harm to human health and life.